Heat stroke-induced Guillain–Barré syndrome: a case report and literature review - Pang, Yang; Li, Feijie; Li, Si; Yuan, Jiaojiao (Frontiers in Disaster and Emergency Medicine, 2025)
In recent years, there has been an increase in complications related to heat stroke (HS), especially those affecting the neurological system. The co-occurrence of HS and Guillain–Barré syndrome (GBS) is exceptionally rare, with fewer than 15 documented cases. This case report describes a patient who developed GBS following an HS and includes a literature review that highlights the rarity of this neurological complication. This study aimed to increase awareness and aid in clinical decision-making regarding the management of classic HS.